Cover Feature: Hydroxy‐Functionalized Hypercrosslinked Polymers (HCPs) as Dual Phase Radioactive Iodine Scavengers: Synergy of Porosity and Functionality (ChemPlusChem 11/2022). Issue 11 (27th September 2022) - Samanta, Partha; Dutta, Subhajit; Let, Sumanta; Sen, Arunabha; Shirolkar, Mandar M.; Ghosh, Sujit K.
Abstract : The cover feature image illustrates a family of hydroxy‐functionalized hypercrosslinked polymers (HCPs) toward efficient capture of radioactive iodine from both vapour and water phase. The polymeric scavengers were also utilized to establish the first case of functionality and porosity synergy in this kind of material for radioactive iodine removal; a key advancement from the energy‐economy standpoint of real‐time radioactive contaminant sequestration. More information can be found in the Research Article by Sujit K. Ghosh and co‐workers .